Answer:
Option B is correct.
Average rate of change from x=1 to x=2 is 3
Explanation:
Formula for Average rate of change: The ratio of the difference in the function f(x) as it changes from a to b to the difference between a and b :
![A(x) = (f(b)-f(a))/(b-a)](https://img.qammunity.org/2019/formulas/mathematics/college/gkzxe07ffq42gdwj4k8lj2ay8gqkqndbix.png)
As per the statement:
![f(x) = 4^(x-1) +2](https://img.qammunity.org/2019/formulas/mathematics/college/vo18uct177lywk4ls0a9j3n6gcyocubyw9.png)
Calculate the average rate of change from x =1 to x =2
At x = 1
![f(1) = 4^(1-1) +2 = 1 +2 = 3](https://img.qammunity.org/2019/formulas/mathematics/college/1p63qeqzy7v9po5l1t4yltqmtacqr5kh68.png)
At x = 2
![f(2) = 4^(2-1) +2 = 4^1 +2 = 4+2 =6](https://img.qammunity.org/2019/formulas/mathematics/college/nb7n3ms3w8vb1hbmmps2sb6jbtbferdik1.png)
Then;
![A(x) = (f(2)-f(1))/(2-1) = (6-3)/(1) =(3)/(1) = 3](https://img.qammunity.org/2019/formulas/mathematics/college/4mt92cdx3k683tek1f90jfflwgrsyopbl0.png)
Therefore, the average rate of change from x=1 to x=2 is 3